2022
DOI: 10.3389/feduc.2022.964456
|View full text |Cite
|
Sign up to set email alerts
|

Social media usage and acceptance in higher education: A structural equation model

Abstract: The adoption and use of social media as an educational technology in higher education has been exacerbated during the COVID-19 pandemic. As a result, this study applied the unified theory of usage and acceptance of technology theory and the technology acceptance model as predictors of behavioral intention to use social media and actual social media use. These, as posited by the model, affect the performance impact of social media usage. This study involved a quantitative survey with 312 undergraduate universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 85 publications
(108 reference statements)
1
11
0
Order By: Relevance
“…Adoption and implementation of new technologies required to develop e-learning in HEIs take time, require training, and require subjective norms and an institutional willingness to accept new technologies. Surprisingly, [ 21 , 22 ] discovered that innovative technologies alone cannot produce the desired academic changes; ongoing human investment in training is also required. According to Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Adoption and implementation of new technologies required to develop e-learning in HEIs take time, require training, and require subjective norms and an institutional willingness to accept new technologies. Surprisingly, [ 21 , 22 ] discovered that innovative technologies alone cannot produce the desired academic changes; ongoing human investment in training is also required. According to Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Affecting an assessment chief in such as now emphatically one-sided networks will have a less critical effect on the item. (A. M. Al-Rahmi et al, 2022;Alismaiel et al, 2022).…”
Section: Social Media Marketingmentioning
confidence: 99%
“…According to Goodhue and Thompson (1995), technology characteristics are posited to have a significant effect on task-technology fit. In a study with 206 Malaysian students to examine the factors affecting academic performance in higher education using the Task-technology Fit model, it was found that technology characteristics have a significant Journal of Applied Learning & Teaching Vol.6 No.1 ( 2023) effect on task-technology fit (Al-Rahmi et al, 2020).…”
Section: The Proposed Research Modelmentioning
confidence: 99%